THE IMPACT OF REGIONAL AUTONOMY ON REGIONAL DEVELOPMENT - Budijaya, M. Ikrar; Heryanto, Yanto (International Journal of Social Service and Research, 2024)
The objective of this research is to analyze the impact of regional autonomy on regional development. This study aims to understand how the implementation of regional autonomy policies, which grant greater authority to local governments in managing resources and making decisions, influences various aspects of regional development. The research focuses on assessing the effectiveness of regional autonomy in improving the quality of public services, local economic growth, and equitable development. The research method employed in this study is literature review, involving the collection and analysis of data from various written sources such as books, journals, articles, and other relevant documents related to the research topic. Data analysis techniques are conducted through literature studies, where the researcher reviews, compares, and synthesizes information obtained from various sources. The results of this study indicate that the implementation of regional autonomy, which provides greater authority to local governments in managing regional affairs, has various positive impacts and challenges for regional development. The success of regional autonomy largely depends on the capacity of local governments to manage the given authority and synergy with the central government in achieving sustainable development goals.